Uganda : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Uganda reached the completion point under the enhanced HIPC Initiative on May 1, 2000. Staff is of the view that all criteria are met, and recommends that the Board determine that Uganda qualifies for immediate debt relief under the MDRI.